2019
DOI: 10.1186/s13034-019-0305-0
|View full text |Cite
|
Sign up to set email alerts
|

Looking into the crystal ball: quality of life, delinquency, and problems experienced by young male adults after discharge from a secure residential care setting in the Netherlands

Abstract: BackgroundAdolescents in residential care are a vulnerable population with many problems in several life areas. For most of these adolescents, these problems persist after discharge and into adulthood. Since an accumulation of risk factors in multiple domains increases the likelihood of future adverse outcomes, it would be valuable to investigate whether there are differences in life after residential care between subgroups based on multiple co-occurring risk factors.Aims and hypothesisThe aim of this explorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(59 reference statements)
1
0
0
Order By: Relevance
“…Another significant factor influencing anti-social behavior in adolescents is the presence of mental abnormalities [9]. Our research has also shown that there are both healthy adolescents and those with mental abnormalities among the pupils at CTSEI (the analogue of safe residential institutions).…”
Section: Discussionsupporting
confidence: 54%
“…Another significant factor influencing anti-social behavior in adolescents is the presence of mental abnormalities [9]. Our research has also shown that there are both healthy adolescents and those with mental abnormalities among the pupils at CTSEI (the analogue of safe residential institutions).…”
Section: Discussionsupporting
confidence: 54%